2019
DOI: 10.1007/s11906-019-0996-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness and Challenges of Implementing Intensive Blood Pressure Goals and Team-Based Care

Abstract: Purpose: Review the effectiveness, cost-effectiveness, and implementation challenges of intensive blood pressure (BP) control and team-based care initiatives. Recent Findings: Intensive BP control is an effective and cost-effective intervention, yet implementation in routine clinical practice is challenging. Several models of team-based care for hypertension management have been shown to be more effective than usual care to control BP. Additional research is needed to determine the cost-effectiveness of team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…The panel discussed what must be done to improve healthcare access and “meet patients where they are.” Implementation of proven and effective patient‐centered strategies (such as team‐based and protocolized care with pharmacists and nurses, as well as home BP monitoring) are needed. 33 , 34 The impressive results of the BARBER trial were discussed. In a cluster‐randomized design, the BARBER trial randomly assigned 78 Los Angeles County predominantly Black barbershops and 319 Black male patients to 1 of 2 interventions: (1) a clinical pharmacist‐led intervention, in which Black barbers encouraged patrons with uncontrolled hypertension to meet with specialty‐trained clinical pharmacists who initiated, monitored, and intensified antihypertensive medication therapy, or (2) an active‐control approach, where barbers encouraged lifestyle modification and doctor appointments only to manage hypertension.…”
Section: Next Steps To Make Progressmentioning
confidence: 99%
See 2 more Smart Citations
“…The panel discussed what must be done to improve healthcare access and “meet patients where they are.” Implementation of proven and effective patient‐centered strategies (such as team‐based and protocolized care with pharmacists and nurses, as well as home BP monitoring) are needed. 33 , 34 The impressive results of the BARBER trial were discussed. In a cluster‐randomized design, the BARBER trial randomly assigned 78 Los Angeles County predominantly Black barbershops and 319 Black male patients to 1 of 2 interventions: (1) a clinical pharmacist‐led intervention, in which Black barbers encouraged patrons with uncontrolled hypertension to meet with specialty‐trained clinical pharmacists who initiated, monitored, and intensified antihypertensive medication therapy, or (2) an active‐control approach, where barbers encouraged lifestyle modification and doctor appointments only to manage hypertension.…”
Section: Next Steps To Make Progressmentioning
confidence: 99%
“… 42 , 43 To do so, we must invest in increasing the implementation of and providing greater access to proven highly effective team‐based care models for hypertension. 32 , 33 We have a steep climb ahead. A recent report found that 40% of patients with uncontrolled hypertension are only taking one antihypertensive medication.…”
Section: Next Steps To Make Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, further studies are however still needed to evaluate, at large scale, how to implement efficiently this TBC model, for example by economic analyses, integrating cost and time estimations to provide the TBC intervention ( 41 ). These studies may offer policymakers additional compelling arguments and open good perspectives for an extensive implementation of the TBC model.…”
Section: Conclusion and Further Perspectivementioning
confidence: 99%
“…In general, SBP reduction is linearly correlated with the risk of developing cardiovascular diseases and death, with the lowest risk at approximately 120-124 mmHg [4]. Moreover, reducing SBP to less than 130 mmHg has been shown to contribute to a reduced risk of cardiovascular disease events [5]. The "Guidelines for the management of hypertension, 2019" published by…”
Section: Introductionmentioning
confidence: 99%